1992
DOI: 10.1128/iai.60.6.2397-2401.1992
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Aotus monkeys from malaria infection by immunization with recombinant hybrid proteins

Abstract: On the basis of investigations of the malarial blood-stage antigens SERP, HRPII, and MSAI from Plasmodium fakciparum, we chose two Escherichia coli-expressed hybrid proteins containing selected partial sequences of these antigens. Antibodies raised against both hybrid proteins in rabbits and Aotus monkeys recognize the corresponding P. fakciparum polypeptides. In two independent trials with 13 animals, immunization of Aotus monkeys with either of the two hybrid proteins administered in a well-tolerated oil-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
2

Year Published

1992
1992
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 23 publications
2
18
2
Order By: Relevance
“…High immunogenicity [123] SERP/HRP2/MSP-1 Preclinical (Aotus) Two hybrid recombinant proteins Protection in one study, nonprotection in the other [111,112] and coworkers, in the 1960s, showed that an immunization procedure could induce sterile protection against malaria. In fact, the injection of irradiated sporozoites in mice [41], nonhuman primates [42] or humans [43] was shown to fully protect the host against a subsequent challenge with infectious sporozoites.…”
Section: Sporozoitementioning
confidence: 99%
See 1 more Smart Citation
“…High immunogenicity [123] SERP/HRP2/MSP-1 Preclinical (Aotus) Two hybrid recombinant proteins Protection in one study, nonprotection in the other [111,112] and coworkers, in the 1960s, showed that an immunization procedure could induce sterile protection against malaria. In fact, the injection of irradiated sporozoites in mice [41], nonhuman primates [42] or humans [43] was shown to fully protect the host against a subsequent challenge with infectious sporozoites.…”
Section: Sporozoitementioning
confidence: 99%
“…Human vaccine trials have been conducted with combinations of recombinant MSP-1, MSP-2 and RESA in the Montanide ISA720 adjuvant, with the most recent being a Phase IIb trial in children in a highly endemic area of Papua New Guinea [73]. A hybrid molecule containing the blood-stage antigens SERP, MSP-1 and HRP-2 has been tested in Aotus, and the results were controversial in two different studies, with protection being showed in the first [111] but not in the second [112].…”
Section: Multistage Approachesmentioning
confidence: 99%
“…Two recombinant Escherichia coli-expressed hybrid proteins both containing partial sequences of SERA and histidine-rich protein II and one also containing MSP-1 were used to immunize Aotus monkeys. These monkeys were protected from subsequent challenge with P. falciparum (50). The SERA sequence contained in these recombinant proteins was subsequently shown to be conserved in six P. falciparum isolates from various parts of the world (52).…”
Section: Merozoite and Erythrocytic Antigensmentioning
confidence: 99%
“…Our laboratories have been working with malaria transmission and immunity, and in this context our research has focused on the humoral immune response against P. falciparum antigens (Banic et al 1994, Ferreira-da-Cruz et al 1995. One such antigen is p126, a molecule that has been shown to induce protective immunity in monkeys (Delplace et al 1988, Knapp et al 1992. With a view to bypassing the problems mentioned above we compared the antigenicity of p126 P. falciparum peptides with predicted antigenic regions identified using the methods described by Garnier et al 1978, Chou & Fasman 1974.…”
Section: Introductionmentioning
confidence: 99%